Дворянское гнездо - Тургенев Иван Сергеевич (АСТ, 2011)
Экземпляры: ф.6 (20211011) / Инвентарный номер: 3699 И / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: Т 87 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)1-44